2019
DOI: 10.1029/2019jc015197
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Sediment Flocculation in Langmuir Turbulence

Abstract: Cohesive sediments exist as flocs of different sizes, which are built and destroyed through flocculation processes including both aggregation and breakup. This study investigates sediment flocculation processes in wave-driven Langmuir turbulence that is commonly observed in coastal ocean through embedding a size-resolving flocculation model into a turbulence-resolving hydrodynamic model. The specific research questions are how Langmuir turbulence affects flocculation processes and how flocculation processes im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 116 publications
0
7
1
Order By: Relevance
“…of metal flocs. 30,31 Previous EC studies reported smaller BET surface areas (19.8–84.1 m 2 g −1 ) of zinc hydroxide floc generated by EC than the present study. 14,32,33 The difference is likely due to the different aeration conditions, a different configuration of the EC reactor, different initial pH, and the presence of different dissolved ions in the solution.…”
Section: Resultscontrasting
confidence: 77%
“…of metal flocs. 30,31 Previous EC studies reported smaller BET surface areas (19.8–84.1 m 2 g −1 ) of zinc hydroxide floc generated by EC than the present study. 14,32,33 The difference is likely due to the different aeration conditions, a different configuration of the EC reactor, different initial pH, and the presence of different dissolved ions in the solution.…”
Section: Resultscontrasting
confidence: 77%
“…The matching between the analytical and numerical solutions has been illustrated through some various figures (Figs. 1,2,3,4,5,6). The applied numerical method's performance shows its powerful and effective for studying the numerical solutions of some nonlinear evolution equations.…”
Section: Discussionmentioning
confidence: 99%
“…This magnitude is based totally on its achievement according to supplying a profitable probability in conformity with overmatch the concentration Problem within Langmuir [3,4]. The concentration trap in Langmuir is attributable according to the enlarge within the number concerning long-wave disruptions between who the vibrance do no longer stay damped by means of Landau yet radiation; the connection together with the coulomb at intense instances is similarly incapable of airing the smearing editions within the oscillations because concerning their frequency [5][6][7]. Plasma sickness has grown to be a regime over extreme longevity up to expectation approves condensing fluctuations in imitation of remain released, addresses the trouble regarding the Langmuir turbulence power a e-mail: mostafa.khater2024@yahoo.com (corresponding author) 0123456789().…”
Section: Introductionmentioning
confidence: 99%
“…The effect of differential settling on the aggregation process is relatively greater in weak turbulence regions, for example, still water in laboratory experiments (Wendling et al, 2015) and estuarine and coastal environments during slack waters (Christie et al, 1999;Guo et al, 2017;Guo et al, 2018;Milligan et al, 2007). Of these three principle particle collision mechanisms, fluid shear is the dominant mechanism that drives particle collision in energetic flows (Liu et al, 2019;Manning, 2004;McAnally William and Mehta Ashish, 2000). Other factors can also influence the particle collision, such as suspended sediment concentration (SSC) (Manning, 2004;Mhashhash et al, 2018;Razaz et al, 2015;Tran et al, 2018;Van der Lee, 2000).…”
Section: Introductionmentioning
confidence: 99%